ANALISIS STRUKTUR PASAR DAN DAYA SAING EKSPOR KAYU MANIS (Cinnamomum burmannii) INDONESIA DALAM PERDAGANGAN INTERNASIONAL - Riptanti, Erlyna Wida; Kurniawati, Atila Windi; Handayani, Sugiharti Mulya (Jurnal Agristan, 2024)
Indonesia is recognized as one of the world's leading cinnamon producers, boasting competitive capabilities in the global cinnamon trade. Despite a decline in export volume, the value and export prices of Indonesian cinnamon tend to increase. Therefore, this study aims to comparatively analyze the market structure and export competitiveness of Indonesian cinnamon in international trade using secondary data. To evaluate the market structure, several analysis methods are used including the Concentration Ratio (CR4), Herfindahl Index (HI), Revealed Comparative Advantage (RCA), Export Product Dynamic (EPD), and Trade Specialization Index (TSI). This results shows that the cinnamon market in international trade can be characterized as an oligopolistic competitive market with a notable level of concentration. Indonesian cinnamon shows both comparative and competitive advantages in the global market, occupying a Rising Star position in the United States, a Falling Star position in India, a Lost Opportunity position in Vietnam, and a Retreat position in the Netherlands and German markets respectively. Indonesian cinnamon is in the maturity stage with an average TSI value of 0.90, and Indonesia tends to be an exporting country. In terms of market potential, the United States emerges as the most promising market for developing Indonesian cinnamon, with considerable opportunities also present in the Indian and Vietnamese markets. Conversely, the Netherlands and German markets show comparatively less potential for growth and development. The study recommends that efforts to increase the volume of Indonesian cinnamon exports should be focused on increasing domestic cinnamon production both in terms of quality and quantity.